Engineering mycelium fungi into an effective char-forming thermal protection material via alkaline deacetylation. (June 2023) - Chulikavit, Nattanan; Huynh, Tien; Wang, Cheng; Yuen, Anthony Chun Yin; Khatibi, Akbar; Mouritz, Adrian; Kandare, Everson
Abstract: The char yield from mycelium fungi can be improved via alkaline deacetylation wherein chitin polymer segments are converted to chitosan moieties. The influence of alkaline deacetylation conditions (e.g., temperature, incubation time and alkali concentration) on the biochemical composition, microstructural and physicochemical characteristics and thermal properties of mycelium fungi is poorly understood. In this paper, we investigated the influence of different alkaline deacetylation conditions on the degree of deacetylation and thermal properties of non-pathogenic Basidiomycota phylum, mycelium fungi, grown in molasses. Particularly, we determined the relationship between the degree of deacetylation and high-temperature char-forming characteristics of deacetylated mycelium. Further, the effect of an oxidizing agent, KMnO4, on the thermal stability and char-forming characteristics of alkaline-treated mycelium was investigated. This paper presents a comprehensive investigation of the relationship between the degree of deacetylation and char yields at high temperatures (e.g., >300°C) as well as an in-depth interrogation of the thermal degradation mechanisms governing the thermal stability of alkaline (and KMnO4 ) treated mycelium. Research findings from this study have advanced knowledge of the development and design of bio-derived thermal protection materials for fire-threatened infrastructure. Graphical abstract: Image, graphical abstract